2012
DOI: 10.1002/ppul.22536
|View full text |Cite
|
Sign up to set email alerts
|

Development of reference equations for spirometry in japanese children aged 6–18 years

Abstract: We recommend the use of this new set of prediction equations together with suggested cut-off values, for assessment of spirometry in Japanese children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
5
35
1
2
Order By: Relevance
“…12 Consistent with previous reports,4–11 14 23 24 we confirmed that the NICHD classification of BPD14 was useful for predicting the impairment of long-term lung function (table 2). …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…12 Consistent with previous reports,4–11 14 23 24 we confirmed that the NICHD classification of BPD14 was useful for predicting the impairment of long-term lung function (table 2). …”
Section: Discussionsupporting
confidence: 91%
“…Lung function results with respective BPD classification are shown in table 2. After adjustment for age, sex and height using a reference for Japanese children,12 children who were born ELBW had a lower baseline spirometry, as shown by a reduction in the per cent predicted compared with the reference for Japanese children. There was a trend towards a decreased level of all lung function variables, except for FEV 1 /FVC ratio, as the grade of BPD increased.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Table 4 compared the predicted values of FVC, FEV 1 , PEF and MMEF obtained from the developed equations and the existing reference prediction equations of Kui Feng et al [11], Meng-Chiao Tsai et al [8], Masato Takase et al [26], John Hankinson et al [27], and Mary S. M. Ip et al [6] based on the validation subset. No significant difference was found in males, indicating the developed predictive models were comparable to the existing ones in males, whereas in females non-significance was found only for PEF.…”
Section: Resultsmentioning
confidence: 99%